Adolescents Just Do Not Know What They Want: A Qualitative Study to Describe Obese Adolescents' Experiences of Text Messaging to Support Behavior Change Maintenance Post Intervention - Smith, Kyla L; Kerr, Deborah A; Fenner, Ashley A; Straker, Leon M (JMIR Publications, 2014)
BackgroundAdolescents are considered a hard to reach group and novel approaches are needed to encourage good health. Text messaging interventions have been reported as acceptable to adolescents but there is little evidence regarding the use of text messages with overweight and obese adolescents to support engagement or behavior change after the conclusion of a healthy lifestyle program. ObjectiveThe intent of this study was to explore the opinions of overweight adolescents and their parents regarding the use of text messages as a support during the maintenance period following an intervention. MethodsThis paper reports on the findings from focus groups conducted with adolescents (n=12) and parents (n=13) who had completed an eight-week intensive intervention known as Curtin University's Activity, Food and Attitudes Program (CAFAP). Focus groups were conducted three months post intensive intervention. Participants were asked about their experiences of the prior three-month maintenance phase during which adolescents had received tri-weekly text messages based on the self-determination theory and goal-setting theory. Participants were asked about the style and content of text messages used as well as how they used the text messages. Data were analyzed using content and thematic analyses. ResultsTwo clear themes emerged from the focus groups relating to (1) what adolescents liked or thought they wanted in a text message to support behavior change, and (2) how they experienced or responded to text messages. Within the "like/want" theme, there were five sub-themes relating to the overall tone of the text, frequency, timing, reference to long-term goals, and inclusion of practical tips. Within the "response to text" theme, there were four sub-themes describing a lack of motivation, barriers to change, feelings of shame, and perceived unfavorable comparison with other adolescents. What adolescents said they wanted in text messages often conflicted with their actual experiences. Parent reports provided a useful secondary view of adolescent experience. ConclusionsThe conflicting views described in this study suggest that overweight and obese adolescents may not know or have the ability to articulate how they would best be supported with text messages during a healthy lifestyle maintenance phase. Further, supporting both engagement and behavior change simultaneously with text messaging may not be possible. Intervention texts should be personalized as much as possible and minimize feelings of guilt and shame in overweight and obese adolescents. Future research with text messaging for overweight and obese adolescents should incorporate clear intervention aims and evaluation methods specifically related to adolescent engagement or behavior change. Trial RegistrationAustralian New Zealand Clinical Trials Registry: ACTRN12611001187932; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12611001187932 (Archived by WebCite at http://www.webcitation.org/6LGSbk8d9).